2012
DOI: 10.1073/pnas.1120860109
|View full text |Cite
|
Sign up to set email alerts
|

Sex, puberty, and the timing of sleep EEG measured adolescent brain maturation

Abstract: The steep adolescent decline in the slow wave (delta, 1-4 Hz) electroencephalogram (EEG) of nonrapid eye movement (NREM) sleep is a dramatic maturational change in brain electrophysiology thought to be driven by cortical synaptic pruning. A perennial question is whether this change in brain electrophysiology is related to sexual maturation. Applying Gompertz growth models to longitudinal data spanning ages 9-18 y, we found that the timing of the delta decline was significantly (P < 0.0001) linked to timing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 19 publications
3
80
1
5
Order By: Relevance
“…A potential role for an adrenal-derived hormone in the decline in delta power during adolescence was suggested by Campbell et al based on the strong association between the age of most rapid delta decline and the age of most rapid increase in pubic hair in girls. 8 Note that while the same association was observed in the boys in that study, pubic hair develops in boys in response to both testicular and adrenal-derived androgens, whereas in girls with normally-timed puberty, pubic hair typically reflects adrenarche. Furthermore, whereas DHEAS has been shown to act centrally in animal models, 35 in humans, DHEAS in peripheral blood does not easily penetrate the blood brain barrier.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A potential role for an adrenal-derived hormone in the decline in delta power during adolescence was suggested by Campbell et al based on the strong association between the age of most rapid delta decline and the age of most rapid increase in pubic hair in girls. 8 Note that while the same association was observed in the boys in that study, pubic hair develops in boys in response to both testicular and adrenal-derived androgens, whereas in girls with normally-timed puberty, pubic hair typically reflects adrenarche. Furthermore, whereas DHEAS has been shown to act centrally in animal models, 35 in humans, DHEAS in peripheral blood does not easily penetrate the blood brain barrier.…”
Section: Discussionmentioning
confidence: 75%
“…In studies that included both physician-determined Tanner staging of puberty and PSG sleep studies at 6-month intervals, Campbell et al found that the age of most rapid delta decline was in fact related to the age of most rapid pubertal maturation, favoring a causal role for sex steroids. 8 Further, men with congenital GnRH deficiency who fail to undergo puberty have more SWS than age-matched controls and demonstrate a decrease in SWS after treatment with testosterone, 9,10 providing further support for the hypothesis that sex steroids may modulate sleep staging and depth.…”
Section: Introductionmentioning
confidence: 73%
“…Additional data from the same subjects (Campbell et al, 2012) showed that although the rate of the delta decline was not associated with the rate of pubertal maturation, the timing of both maturational processes was related -a highly significant relation between the age of most rapid pubertal maturation and the age of most rapid delta decline has been observed. It was also demonstrated that this timing relationship was independent of sex differences, i.e., the earlier delta power decline in girls compared to boys (Campbell et al, 2012). The authors suggest that the timing of cortical synaptic pruning, considered as the most possible cause of delta decline, is strongly related to the timing of puberty.…”
Section: Nrem Delta Decline and Pubertal Maturationmentioning
confidence: 89%
“…The steep decline in slow-wave sleep at around the time of puberty is considered a milestone in physiological brain maturation [48]. This is a critical window during which DSPD symptoms can emerge, which could be taken as circumstantial theory that changes in sleep homeostatic factors, and their differential emergence during puberty, may also play a role in the disorder's pathophysiology [49].…”
Section: Sleep Homeostatic Mechanismmentioning
confidence: 99%